Produção enzimática de compostos de valor agregado a partir do destilado da desodorização do óleo de soja - Vieira, Ana Carolina (2021)
The use of by-products (or residues) is sought in an industrial process in order to transform them into a value-added product. In the soybean oil refining industry, deodorization distillate (SODD) is a by-product with great biotechnological potential due to its high content of glycerides and tocopherol. This work aimed to evaluate the potential application of SODD in the production of biodiesel and xylose fatty ester (ester with surfactant/emulsifying properties) through the enzymatic route. SODD was physicochemically characterized, presenting a high saponification index due to the high content of acylglycerides (approximately 85 wt.%), mainly long-chain (C18). An experimental design showed that temperature of 35 °C, enzyme concentration of 8.36 wt.% and molar ratio of 3.64: 1 (ethanol: SODD-SP) were found as the best conditions for the production of fatty acid ethyl esters (FAEEs) from the SODD saponifiable phase (SODD-SP), yielding a product with up to 90.8 wt.% ester yield after caustic treatment to reduce free fatty acids. The SODD saponifiable phase was hydrolyzed with free lipases and, later, the free fatty acid rich material was used to produce ethyl esters and xylose fatty esters. The hydrolysis step yielded saponifiable materials with 72.5 wt.% and 84.4 wt.% of free fatty acids (FFAs) after 48 h of hydrolysis using the lipases Eversa (liquid lipase formulation of Thermomyces lanuginosus from Novozymes A/S) and PFL (Pseudomonas fluorescens lipase), respectively. The simultaneous esterification and transesterification reaction of the latter material with ethanol yielded a product with 81.5 wt.% of esters, 8.3 wt.% of unconverted glycerides and 10.2 wt.% of FFAs. In the case of xylose ester syntheses, the immobilized lipases used allowed to obtain xylose conversions of up to 89.2% (using PFL in this case). The behavior of the consumption of xylose and FFAs suggested that a mixture of mono-, di- and triesters was produced, containing mainly unsaturated alkyl fractions linked to xylose. The emulsifying capacities (EC up to 12%) showed potential application of the crude products as biosurfactants.